KONTEKSTUALISASI PEMBELAJARAN SEJARAH ISLAM DALAM MENJAWAB KRISIS AKHLAK DI ERA SOCIETY 5.0 - Pratama, M. Rafi Putra (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
The study of Islamic history plays an important role in shaping the morals of both individuals and society. Through exemplary stories of the Prophet Muhammad (peace be upon him), his companions, and prominent figures in Islamic civilization, Islamic history serves not only as a record of past events but also as a source of moral and spiritual values that can be applied in daily life. This research uses a qualitative method through a literature study approach by analyzing various scholarly references such as journals, books, and relevant articles. The findings indicate that methods such as exemplary behavior, advice (mau’idzah), habituation, storytelling, as well as punishment and reward, are effective approaches in instilling Islamic moral values. Challenges in the era of globalization such as cultural value decline, negative influences of social media and technology, and the lack of early religious education pose serious obstacles to the implementation of moral values. Therefore, the teaching of Islamic history must be optimized not only in academic settings but also within social and family spheres. Islamic history holds great potential as a means of moral transformation, capable of shaping a generation with Islamic character, noble morals, and the ability to adapt to modern challenges without losing their religious identity.